Contribution of Parental Attention and Peer Association toward Adolescent Students’ Character - Aziz, Helmi (UPI Press, 2019)
Teenagers are the age of identity and character formation. This study aims to analyze the contribution of parental attention and peer association toward students’ character. A descriptive study with a quantitative approach, the study involved a population of teenage (eighth grade) students at SMP (Junior High School) Al-Azhar Syifa Budi Parahyangan in the academic year 2018/2019. A total of 48 students were selected through purposive sampling. Data were collected through questionnaire and analyzed with correlation and regression tests. The results showed significant contribution of parental attention and peer association to the students’ character. The implications of this research are addressed to parents, teachers, and school as the parties responsible for the character building of teenage students.